PARTISIPASI POLITIK MASYARAKAT PEDESAAN DALAM PEMILIHAN GUBERNUR JAWA TENGAB TAHUN 2008 (Studi Kasus mengenai Partisipasi Politik Masyarakat Pedesaan di Kecamatan Karanggede, Boyolali dalam Pilgub Jateng 2008) - Wijaya, Sri Herwindya Baskara (Jurnal The Messenger, 2009)
Every citizen has interest and preference on who should command him/her and on the public policy. The directly election of local leader is part of citizen contribution to the public policy corresponding to the Act No. 32 of 2004 about Local Government. That the governor and vice governor position is not based on the election mechanism by DPRD like the previous age. Thus, the society is political participation has a very important role here. Based on the result of research shows that generally, the rural society in subdistrict Karanggede Boyolali has the lower participation level in the Central Java’s Governor of 2008.